Whole house budget-friendly DIY. (Home Services Publications, a subsidiary of Trusted Media Brands, Inc., 2024)
This illustrated guide contains step-by-step guidance from the page of Family Handyman magazine on how to affordably complete home upgrades contains over 320 tips to help update your kitchen, bathroom, garage, yard and more.